Deteksi Dini Gangguan Mental dan Emosional pada Anak yang Mengalami Kecanduan Gadget - Dwi Wulandari; Dilfera Hermiati (Jurnal Keperawatan Silampari, 2019)
This study aims to conduct early screening and the incidence of mental and emotional disorders aimed at children who are addicted to gadgets aged 3-6 years. The research method uses descriptive analytic by looking at the description of the incidence of mental and emotional disorders in children aged 3-6 years. The results showed of 100 respondents as many as 66 (66%) respondents with a high level of addiction, 34 (34%) respondents with a low level of addiction. as many as 41 (41%) respondents with Mental and emotional Normal, 59 (59%) respondents with suspected mental and emotional disorders. Conclusion, most children are addicted to gadgets and most children are at risk of experiencing social problems if parents do not act wisely in the use of gadgets. Keywords: Emotional Mental Disorders, Gadgets Addiction